North Atlantic Regional Water Resources Study. Appendix J. Land Drainage. - CORPS OF ENGINEERS NEW YORK NORTH ATLANTIC DIV (1972)
Appendix J provides general information relating to land drainage and identifies and evaluates potential land drainage needs, and measures for meeting these needs. The resulting costs and benefits of these potential solutions are also developed, as are their overall effects on the Region. Information developed herein has been utilized in the plan formulation process for developing alternative water and related land resources development and management programs for the NAR. The Land Drainage Appendix covers the extent of major and agricultural drainage problems, land drainage improvements, and their economic and hydrologic effects to a degree of refinement consistent with developed guidelines for comprehensive Type I framework studies. Information on land use and yields of areas adversely affected by excess water, production costs and returns, existing and potential land drainage improvements, and fish and wildlife wetland development provided assistance in analyzing and correlating the drainage data to all aspects of water and related land use. Appendix J to report dated Jun 72, AD-A036 616. See also Appendix K, AD-A036 632.